-6z+6+7z=11

Simple and best practice solution for -6z+6+7z=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6z+6+7z=11 equation:


Simplifying
-6z + 6 + 7z = 11

Reorder the terms:
6 + -6z + 7z = 11

Combine like terms: -6z + 7z = 1z
6 + 1z = 11

Solving
6 + 1z = 11

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 1z = 11 + -6

Combine like terms: 6 + -6 = 0
0 + 1z = 11 + -6
1z = 11 + -6

Combine like terms: 11 + -6 = 5
1z = 5

Divide each side by '1'.
z = 5

Simplifying
z = 5

See similar equations:

| x^4-x^3-5x^2=0 | | 427-51x=180 | | 4x+7(x-9)=69 | | x+0.07x=282.68 | | -14-4r=-2+8r | | 6x+y=27 | | 7k+8+8k=11+5+4k+3k | | 5y-3y=27 | | 3x+7(5x-5)=193 | | 2t+-1=3t+7 | | 3b-5=-7+2b | | 5x+4y=63 | | 4f+x-4=-4 | | 18=-4x-5x | | 5x+6(3x-15)=117 | | 2x+2(2x+5)=250 | | 3x+5(0)=30 | | -x=15+30 | | -6=-4p+5p | | 1.50x+0.75=2.00x+0.50 | | 3x+5(-3)=30 | | -15=4b-b | | 1/2x^2=8x−5/8 | | 3x+2(2x+5)=45 | | 3/4*4/5 | | 6-0.5u=11-1.33u | | 3(-5)+5y=30 | | -12=a+6+5a | | log(x)+log(x-15)=2 | | 5x+20=10(x+2)-5x | | 10x-8=136 | | -10=6n-1-3 |

Equations solver categories